2019
DOI: 10.3390/rs11030347
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Multi-GNSS Precise Point Positioning Time and Frequency Transfer with Clock Modeling

Abstract: Thanks to the international GNSS service (IGS), which has provided multi-GNSS precise products, multi-GNSS precise point positioning (PPP) time and frequency transfer has of great interest in the timing community. Currently, multi-GNSS PPP time transfer is not investigated with different precise products. In addition, the correlation of the receiver clock offsets between adjacent epochs has not been studied in multi-GNSS PPP. In this work, multi-GNSS PPP time and frequency with different precise products is fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 19 publications
(31 reference statements)
0
26
0
Order By: Relevance
“…The aim of many recent studies is to increase the positioning accuracy of Global Navigation Satellite Systems (GNSS) by use of the Precise Point Positioning (PPP) technique. The authors of [30] compared a multi-GNSS PPP time and frequency transfer with different precise products. To improve multi-GNSS PPP time and frequency, they suggest employong a receiver clock offset model, considering the correlation of the receiver clock offsets between adjacent epochs using an a priori value.…”
Section: Some Properties Of the Presented Methodsmentioning
confidence: 99%
“…The aim of many recent studies is to increase the positioning accuracy of Global Navigation Satellite Systems (GNSS) by use of the Precise Point Positioning (PPP) technique. The authors of [30] compared a multi-GNSS PPP time and frequency transfer with different precise products. To improve multi-GNSS PPP time and frequency, they suggest employong a receiver clock offset model, considering the correlation of the receiver clock offsets between adjacent epochs using an a priori value.…”
Section: Some Properties Of the Presented Methodsmentioning
confidence: 99%
“…In 2013, Wang et al [ 11 ] demonstrated the feasibility of the stochastic clock parameter with constrained variance in subsequent epochs, and the extent of the improvement was different for different types of atomic clocks. In 2018, Ge et al [ 12 , 13 ] contributed the receiver clock offset model considering the correlation of the receiver clock offsets among adjacent epochs using an a priori value, which is suitable for single GNSS and multiple GNSS. In 2014, Lyu et al [ 14 ] achieved covariance with white frequency modulation (WFM) noise, random walk frequency modulation (RWFM) noise and the correlation between the clock and ambiguity parameter and obtained better results in mitigating day boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…As it is hard to obtain meteorological parameters because of the economic cost, the initial value of tropospheric delay is normally determined based on standard atmospheric parameters [11][12][13][14]; however, as the results obtained have a lower accuracy, a longer convergence period is always required for GNSS positioning. With the increasing application of PPP [15][16][17][18][19], in order to improve the convergence speed of PPP [20,21], the accuracy of the troposphere model needs to be higher.…”
Section: Introductionmentioning
confidence: 99%